Biological denitrification inhibition (BDI) in the field: A strategy to improve plant nutrition and growth. (September 2019) - Galland, William; Piola, Florence; Burlet, Alexandre; Mathieu, Céline; Nardy, Mélisande; Poussineau, Sophie; Blazère, Leslie; Gervaix, Jonathan; Puijalon, Sara; Simon, Laurent; Haichar, Feth el Zahar
Abstract: Nitrogen is one of the factors limiting in plant growth, is naturally present in soils, and is mainly assimilated as nitrate and ammonium by plants. However, soil nitrate is also used by denitrifying bacteria, which reduce it to N2 O (a greenhouse gas) and N2 . Therefore, plants are in direct competition with these bacteria for the assimilation of nitrate. Recently, our research team has highlighted a strategy developed by some plants consisting of the production of secondary metabolites (procyanidins) that inhibit the denitrification activity of microbial communities in soils, referred to as BDI for biological denitrification inhibition (BDI). This strategy could make nitrate more available in the soil, which may then be used by plants for their growth. However, the extent to which procyanidins can affect plant growth and nutrition via BDI under field conditions has not yet been investigated. In this study, we tested the effect of procyanidins exogenously applied in the field on the nutrition and growth of cos or romaine lettuce crops ( Lactuca sativa ) nutrition and growth. Procyanidins were added to growing lettuce at 8, 42, 83 and 210 kg ha −1 . Soil denitrification enzyme activity (DEA), nitrate concentration, above- and below-ground lettuce traits and the abundance of total bacteria and denitrifiers were measured in lettuces treated or untreated with procyanidins. Our results showed that the addition of procyanidins in the field at 210 kg ha −1 resulted in: (1) the inhibition of microbial denitrification activity and counter-selection of denitrifiers in the root-adhering soil of lettuce and (2) an increase in available nitrate and a significant gain in plant productivity. This study allowed us to propose for the short term the development of a more environmentally friendly method of sustainable agriculture by limiting fertilizer inputs, nitrogen losses from the soil, and greenhouse gas emissions while increasing plant growth and productivity. Graphical abstract: Image 1 Highlights: Procyanidins applied in the field did not modify lettuce physiology regardless of the used concentration Significant dose-response relationship between procyanidins concentrations and BDI Procyanidins induce counter-selection of denitrifiers Nitrate was more absorbed by lettuce treated with procyanidins Applied procyanidins successfully increase plant growth yields